Left Dislocation in North-Eastern Neo-Aramaic dialects - Khan, Geoffrey (Stellenbosch Papers in Linguistics Plus, 2016)
The North-Eastern Neo-Aramaic (NENA) dialects, which are the focus of this paper, were spoken across a wide area encompassing northern Iraq, north-west Iran, south-eastern Turkey, Armenia and Georgia. In these spoken dialects a distinction should be made between two major types of Left Dislocation (LD) structures. In one type the initial item is prosodically and grammatically integrated with what follows. The initial item is prosodically integrated in that it is not separated from what follows by an intonation group boundary. The initial item is resumed in the clause by a pronominal affix, as opposed to an independent pronoun or a full nominal. Such initial items have all the semantic and functional properties of normal grammatical subjects. These are referred to as LD1 structures. A distinct type of construction is where the initial item is less integrated prosodically and/or structurally with what follows. This is referred to as an LD2 structure. This includes cases where the initial item is separated from what follows by an intonation group boundary. Another strategy for disjoining the initial item from the rest of the clause is the resumption of the initial item by an independent pronoun. Moreover, an additional structure in which the initial element is less integrated into the clause than LD1 constructions is where the resumptive element is a full nominal rather than a pronoun. An initial item in a LD2 structure is restricted to nominals that are topical, i.e. they function as the informational pivot or starting point of the following clause and typically their referent is identifiable from the context. The initial item of an LD1 structure, however, can have a variety of other types of status, including narrow focus. In this respect they correspond functionally to clause-initial subjects. When a clause-initial item has topical status, whether it be subject, an LD1 item or an LD2 item, the basic function of the construction is to express the onset of a discourse section and, if it occurs within the body of the discourse, a disjunction of some kind from what precedes. This includes not only topic shift, but also other types of discourse shifts, such as foreground to background or change in the level of description. In some cases, an LD1 construction is more normal than a construction with the grammatical subject in initial position, and indeed in some cases it is obligatory. This has given rise to diachronic change whereby the original grammatical subject of the construction has been re-analysed as having a different syntactic status.